Penerapan Model Pembelajaran Project Based Learning Di Sdn Kedungpeluk 2 Sidoarjo - Hanik Mahliatussikah; Ayu Windyawati Puspita Wardani; Rosa Meilina Nurcahyanti; Dian Fitra Aryani (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Abstract: The Implementation of the campus teaching independent learning program from the Ministry of Education and Culture of the Republic of Indonesia Batch II provides opportunities for students to add insight and gain experience in helping the teaching and learning process in elementary schools. Among the target partners is SDN Kedungluk 2, Candi District, Regency. Based on initial observations and direct interaction with students in classroom learning, it is known that students are less enthusiastic and less motivated in learning, making it difficult for teachers to deliver material. This resulted in the condition of the class being not conducive. That's why the PBL (Project Based Learning) model is applied because this model has proven to be successful in making students enthusiastic and competitive in their learning because it involves more exploration, interpretation, synthesis and information to produce various forms of learning outcomes which apparently get a positive response from students. PBL activities carried out included, among others, compiling a cooperation tree, learning the properties of light, collage of heroes, education about covid-19, providing life skill materials, teaching students to use laptops & Microsoft word. Learning that involves a lot of student activities is proven to make students more enthusiastic in learning. Learning by doing is in line with this PBL learning. Keywords: Merdeka Belajar; Learning Model; Project Based Learning Abstrak: Pelaksanaan kampus mengajar program merdeka belajar dari Kementerian Pendidikan dan Kebudayaan Republik Indonesia Angkatan II memberikan kesempatan bagi mahasiswa untuk menambah wawasan dan mendapatkan pengalaman membantu proses belajar mengajar di sekolah dasar. Di antara mitra sasarannya adalah SDN Kedungpeluk 2 Kecamatan Candi Kabupaten. Berdasarkan observasi awal dan interaksi langsung dengan siswa dalam pembelajaran di kelas, diketahui bahwa peserta didik kurang  bersemangat dan kurang termotivasi dalam belajar sehingga menyulitkan guru dalam menyampaikan materi. Hal itu mengakibatkan kondisi kelas menjadi tidak kondusif. Karena itulah model pembelajaran PBL (Project Based Learning) diterapkan karena model ini terbukti berhasil membuta siswa bersemangat dan kompetitif dalam belajarnya karena lebih melibatkan eksplorasi, interpretasi, sintesis dan informasi untuk menghasilkan berbagai bentuk hasil belajar yang terrnyata mendapat respon positif dari peserta didik. Kegiatan PBL yang dilakukan anatara lain, menyusun pohon kerjasama, pembelajaran sifat-sifat cahaya, kolase pahlawan, edukasi tentang covid-19, memberikan materi life skill, mengajarkan siswa menggunakan laptop & microsoft word. Pembelajaran dengan banyak melibatkan aktivitas siswa ini terbukti membuat siswa lebih bersemangat dalam belajar. Learning by doing menjadi sejalan dengan pembelajaran PBL ini. Kata kunci: Merdeka Belajar; Model Pembelajaran; Project Based Learning